Evening whey protein intake, rich in tryptophan, and sleep in elite male Australian Rules Football players on training and nontraining days - Ferguson, C.; Aisbett, B.; Lastella, M.; Roberts, S.; Condo, D. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
Objectives: To investigate the effect of evening whey protein supplementation, rich in tryptophan, on sleep in elite male Australian Rules Football players. Design: Double-blinded, counterbalanced, randomized, cross-over study. Methods: Sleep was assessed using wrist activity monitors and sleep diaries in 15 elite male Australian Football League players on two training and nontraining days following evening consumption of an isocaloric whey protein supplement or placebo in preseason. A 5-day preintervention period was implemented to determine habitual dietary intake and baseline sleep measures. These habitual data were used to inform the daily dietary intake and timing of ingestion of the evening whey protein supplement or placebo on the intervention days. The whey protein supplement or placebo was consumed 3 hr prior to habitual bedtime. Results: Separate one-way repeated-measures analyses of covariance revealed no differences between the whey protein supplement and the placebo on sleep duration, sleep onset latency, sleep efficiency, or wake after sleep onset on either training or nontraining days. Conclusions: Evening whey protein supplementation, rich in tryptophan, does not improve acute sleep duration or quality in elite male Australian Football League players. However, elite athletes may be able to ingest a high protein/energy intake close to bedtime without impairing sleep, which is important for athlete recovery. Future research should investigate the effect of evening protein intake, high in tryptophan, on sleep duration and quality, including sleep staging during periods of restricted sleep and in poor-sleeping athletes.